THE IMPACT OF DIGITAL RECRUITMENT ON INTERNSHIP EMPLOYEES WORKPLACE READINESS - Nurul Azizah; Awang Darmawan Putra (Management and Leadership Study Programme, 2026)
Digital transformation has driven the recruitment and selection process to shift to online systems to improve efficiency and candidate reach. This study aims to analyze the effectiveness and relevance of online systems in recruiting interns at PT. X Pulp and Paper Riau and their impact on employee performance. The research employs a qualitative descriptive approach with case study methods through perspectives of Sociotechnical System (STS), Transaction Cost Economics (TCE), and Resource-Based View (RBV). The results indicate that online systems effectively improve operational efficiency through reduced transaction costs and accelerated recruitment processes. However, the online system still has limitations in assessing certain aspects such as physical condition and candidate honesty. Nevertheless, the performance of the intern employees remains high, with 90% of participants rated good. This high performance reinforces the RBV principle, as the technology relevance gap is compensated by a strict offline evaluation system during internships. This finding indicates that operational effectiveness is achieved, while technology relevance limitations are offset through comprehensive offline assessments during the internship program.